Effect of Climatic Conditions on the Volatile Compounds of the Aerial Parts of Foeniculum vulgare Mill. Issue 4 (4th July 2019) - Punetha, Deepshekha; Tewari, Geeta; Pande, Chitra; Bhatt, Sunita
Abstract: The investigations was based on chemical diversity of the essential oils provide an opportunity to choose oils with preferential flavor and biologically active composition. Aerial part of Foeniculum vulgare collected from five locations namely Moradabad, Tanakpur, Haldwani, Pithoragarh and Didihat at different altitudes (198, 255, 424, 1514 and 1725m) of North India were hydro distilled and analyzed by GC and GC/MS. The essential oil yield ranged from 0.3-0.9 % (w/w). The major compounds were trans- anethole (26.2-85.4 %) and limonene (2.7-51.5 %). The content of limonene was higher in locations with low altitude (Moradabad; 51.5 %, Tanakpur; 40.8 % and Haldwani; 32.2 %) while trans -anethole content was more than 50 % in the plants collected from high altitude locations namely Pithoragarh and Didihat. The noticeable differences in the chemical composition of the oils separated from the aerial parts of F. vulgare were also correlated with the different climatic conditions. The percentage of limonene was observed to be positively correlated with rainfall (r=0.968, P<0.01) and negatively correlated with the altitude of locations (r=0.975, P<0.01).